Bureaucratic Reform in The Village Government - Siti Khoiriah; Luzman Qashmal (Fakultas Hukum Universitas Lampung, 2022)
The state of Indonesia has a grand design and a national time reform roadmap related to good governance 2010-2025. The grand design of Indonesian reform is regulated by presidential regulation no 81 of 2010 and the employee roadmap is regulated by the ministerial regulation of State Apparatus Empowerment and Bureaucratic Reform, overseeing the task of managing the village, namely the village ministry. The purpose of this study was to determine Bureaucratic reform needed to reorganize the bureaucratic process from the highest to the lowest level and make new breakthroughs (innovation breakthroughs) with gradual, concrete, realistic, earnest steps, thinking outside the existing habits/routines (out of the box thinking), a new paradigm shift, and with extraordinary efforts. The method used in data collection is to analyze the data qualitatively by describing the data. The analysis stage starts by collecting data from primary legal materials (Laws and Regulations) by selecting and classifying systematically to find out the general picture of the research. The data that has been collected is analyzed by using descriptive-analytical, analysis qualitatively as well as conceptual approach, constitutional, and historical approaches. The results of this study can be concluded that the implementation should be applied from the center to the regions and villages in Indonesia. Villages also recognize the concept of good governance directly related to the community.